A Brief Discussion of the Effectiveness of Monetary Policy in a Fixed Exchange Rate System With Perfect Capital Mobility and an Analysis of the “Impossible Trinity” Thesis - Carlos Aviña (Expresión Económica, 2016)
The purpose of this essay is to discuss the effectiveness of monetary policy in a fixed exchange rate system with perfect capital mobility and an analysis of the Impossible Trinity thesis, with the IS-LM-BP framework.